Successful Intelligence Among Students In High-Achieving Schools (Journal of the College of Basic Education, 2024)
The current research aims to know the level of successful intelligence among students in high-achieving schools, as well as knowing the level of successful intelligence according to the variables of gender (male-female) and academic grade (first, second, third) in the middle school.A stratified random sample was selected that included (180) male and female students from schools for outstanding students using a stratified random method from schools affiliated with the Baghdad Al-Rusafa 3rd Education Directorate. The successful intelligence scale was constructed and applied by the researcher after following all scientific steps and procedures, which in its final form included (44) items. .The results showed a generally weak level of successful intelligence among the sample of high-achieving schools, while the level of successful intelligence increased slightly in favor of males, and the level was also affected depending on the grade variable.In light of the research results and conclusions, the researcher developed a set of recommendations and proposals.